Repurposing of a drug scaffold: identification of novel sila analogues of rimonabant as potent antitubercular agents - Ramesh, Remya; Shingare, Rahul D.; Kumar, Vinod; Anand, Amitesh; Swetha, B.; Veeraraghavan, Sridhar; Viswanadha, Srikant; Ummanni, Ramesh; Gokhale, Rajesh S.; Reddy, D. Srinivasa (European Journal of Medicinal Chemistry, 2016)
The structural similarity between an MmpL3 inhibitor BM212, and a cannabinoid receptor modulator rimonabant, prompted us to investigate the anti-tubercular activity of rimonabant and its analogues. Further optimization, particularly through incorporation of silicon into the scaffold, resulted in new compounds with significant improvement in anti-tubercular activity against Mycobacterium tuberculosis (H37Rv). The sila analogue 18a was found to be the most potent antimycobacterial compound (MIC, 31 ng/mL) from this series with an excellent selectivity index. (C) 2016 Elsevier Masson SAS. All rights reserved.

Repurposing of old drugs: identification of novel sila analogues of rimonabant as potent antitubercular agents - Ramesh, R.; Shingare, R.; Anand, Amitesh; Veeraraghavan, S.; Viswanadha, S.; Ummanni, R.; Gokhale, R.; Reddy, D. S. (International Journal of Infectious Diseases, 2016)